Prolonged Activated Partial Thromboplastin Time in Adults with Nephrotic Syndrome: A Case Report - Mutiara Ferina; Alvina Alvina; Karina Shasri Anastasya; Deasyka Yastani; Andira Larasari; Rima Anindita Primandari (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Nephrotic syndrome is classically associated with a hypercoagulable state driven by the compensatory hepatic overproduction of procoagulant proteins and platelet hyperreactivity. However, massive proteinuria can rarely disrupt this paradigm, inducing a paradoxical bleeding diathesis that presents a significant clinical challenge. Discussion: A 22-year-old man presented to the emergency department with a two-week history of generalized edema and a recent onset of melena. Laboratory investigations revealed profound hypoalbuminemia (1.1 g/dL) and extraordinary, massive nephrotic-range proteinuria (63.42 g/24 h), accompanied by dyslipidemia and anemia. Coagulation profiling demonstrated a significantly prolonged activated partial thromboplastin time (aPTT) of 51.4 seconds, confirming an active upper gastrointestinal hemorrhage in the setting of ultra-severe nephrotic. He was treated with methylprednisolone, furosemide, candesartan, and simvastatin, together with albumin transfusion for severe hypoalbuminemia. Conclusion: This case highlights a rare hemorrhagic paradox in nephrotic syndrome and underscores the importance of prompt coagulation workup, including a mixing study, when bleeding occurs in a condition typically considered prothrombotic